A Novel Analytical Solutions for Systems of Fractional Differential Equations using the Conformable Fractional Laplace Transform Method - Kadri, Ilhem (Karshi Multidisciplinary International Scientific Journal, 2025)
In this paper, the conformable fractional Laplace transform method for solving systems of fractional differential equations is introduced. Both linear homogeneous and linear nonhomogeneous fractional differential systems, have been considered utilizing the conformable definition of the fractional derivative. The found solutions are plotted in 2D, which also demonstrate how the solutions are close to each other. Additionally, the exact solution for each case is reached as the fractional order goes to 1. Furthermore, Several numerical examples are included to demonstrate the precision and effectiveness of the proposed technique.